Effect of organic manure and inorganic fertilizers on growth, yield attributes and yield of cardamom (Elettaria cardamomum Maton) - Shanthaveerabhadraiah, M Thimmarayappa, K T Shivashankar, S M (Journal of Spices and Aromatic Crops, 2000)
Experiments conducted at Mudigere (Karnataka, India) to study the effect of organic manure and inorganic fertilizers alone and in combination in cardamom (Elettaria cardamomum) indicated that application of 100% inorganic fertilizers increased the number of bearing suckers. Application of 100% inorganic fertilizers resulted in highest panicle production per clump (23.15) and green 'capsule yield (707 kg/ha). Though 100% inorganic fertilizers gave maximum yield which gave a higher benefit cost ratio of 4.19, integrated nutrient management with 25% organic manure + 75% inorganic fertilizers and 50% organic manure + 50% inorganic fertilizers also recorded yields at par with this treatment (609 and 602 kg/ha, respectively) with benefit cost ratios of 3.22 and 3.04, respectively.